Bioaugmentation of pilot-scale slow sand filters can achieve compliant levels for the micropollutant metaldehyde in a real water matrix. (1st March 2022) - Castro-Gutierrez, VM; Pickering, L; Cambronero-Heinrichs, JC; Holden, B; Haley, J; Jarvis, P; Jefferson, B; Helgason, T; Moir, JW; Hassard, F
Highlights: 3/6 metaldehyde degraders attained at least 90% removal in batch tests at 2 µgL −1 . 2 strains attained compliance (0.1 µgL −1 ) in water containing schmutzdecke. Sand filter bioaugmentation with A. calcoaceticus E1 was ineffective at pilot-scale. Addition of sphingobium CMET-H produced compliant water for more than14 d. Abstract: Metaldehyde is a polar, mobile, low molecular weight pesticide that is challenging to remove from drinking water with current adsorption-based micropollutant treatment technologies. Alternative strategies to remove this and compounds with similar properties are necessary to ensure an adequate supply of safe and regulation-compliant drinking water. Biological removal of metaldehyde below the 0.1 µgL −1 regulatory concentration was attained in pilot-scale slow sand filters (SSFs) subject to bioaugmentation with metaldehyde-degrading bacteria. To achieve this, a library of degraders was first screened in bench-scale assays for removal at micropollutant concentrations in progressively more challenging conditions, including a mixed microbial community with multiple carbon sources. The best performing strains, A. calcoaceticus E1 and Sphingobium CMET-H, showed removal rates of 0.0012 µgh −1 10 7 cells −1 and 0.019 µgh −1 10 7 cells −1 at this scale. These candidates were then used as inocula for bioaugmentation of pilot-scale SSFs. Here, removal of metaldehyde by A. calcoaceticus E1, was insufficient to achieve compliant water regardless testing increasing cell concentrations. Quantification of metaldehyde-degrading genes indicated that aggregation and inadequate distribution of the inoculum in the filters were the likely causes of this outcome. Conversely, bioaugmentation with Sphingobium CMET-H enabled sufficient metaldehyde removal to achieve compliance, with undetectable levels in treated water for at least 14 d (volumetric removal: 0.57 µgL −1 h −1 ). Bioaugmentation did not affect the background SSF microbial community, and filter function was maintained throughout the trial. Here it has been shown for the first time that bioaugmentation is an efficient strategy to remove the adsorption-resistant pesticide metaldehyde from a real water matrix in upscaled systems. Swift contaminant removal after inoculum addition and persistent activity are two remarkable attributes of this approach that would allow it to effectively manage peaks in metaldehyde concentrations (due to precipitation or increased application) in incoming raw water by matching them with high enough degrading populations. This study provides an example of how stepwise screening of a diverse collection of degraders can lead to successful bioaugmentation and can be used as a template for other problematic adsorption-resistant compounds in drinking water purification. Graphical abstract: Image, graphical abstract .